Gulf Cooperation Council (GCC) : Economic Prospects and Policy Challenges for the GCC Countries. (Policy Papers; Policy Paper ;, 2013)
The global and regional economic environment remains challenging. Global growth remains tepid, and although some pick-up is expected, risks are tilted to the downside. Recent volatility in financial markets is having a significant impact on some large emerging markets, highlighting the challenges that will be faced in unwinding the Federal Reserve's quantitative easing policy. Geopolitical uncertainties in the Middle East are also high.